Looking at Male Violence - MacCormack, Terry (Canadian Journal of Counselling and Psychotherapy, 1996)
This article examines the three classes of theories traditionally used to explain the causes ofmale violence: physiological, psychological, and sociological. It argues that the search for suchcauses may in the long run be counterproductive, not only for the person who has beenviolated, but for the man who has committed the violence. A treatment approach is thensuggested that helps the violent man to become both accountable and responsible for hisviolence. This involves inviting the man to consider not what appears to be causing his violentbehaviour—something in himself, his background, or in his culture—but rather how thesevery forces might somehow be restraining him from acting respectfullv towards the people in his life.